2018
DOI: 10.17219/acem/84935
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis of selected genes for the detection of early-stage lung cancer using circulating cell-free DNA

Abstract: analysis of selected genes for the detection of early-stage lung cancer using circulating cell-free DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…In addition, the methylation status of HOXA9 was considered relevant for subtyping lung cancer using liquid biopsies [110] or for its early detection in circulating cell-free DNA [58]. HOXA9 hypermethylation was also found to be a tool to identify advanced neck squamous cell carcinomas favoring tumor progression and metastasis [57], predict survival in breast cancer patients, together with HOXA10 hypermethylation [111], and detect early onset of endometrial cancer [58].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
“…In addition, the methylation status of HOXA9 was considered relevant for subtyping lung cancer using liquid biopsies [110] or for its early detection in circulating cell-free DNA [58]. HOXA9 hypermethylation was also found to be a tool to identify advanced neck squamous cell carcinomas favoring tumor progression and metastasis [57], predict survival in breast cancer patients, together with HOXA10 hypermethylation [111], and detect early onset of endometrial cancer [58].…”
Section: Hoxa Genes Methylated In Cancermentioning
confidence: 99%
“…Recently, using integrated methylome analysis Wei et al reported hypermethylation of SPG20, a putative STAT3 target, for non-invasive detection of gastric cancer at an early stage (Wei et al, 2019). Yang et al explored the potential of eight gene panel for non-invasive detection of lung cancer using qMSP and revealed that the promoter methylation of any of the eight gene could detect the disease with a sensitivity of 72% with 91% specificity, reflecting the utility of plasma DNA methylation as a novel approach for detection of lung cancer at early stage (Yang et al, 2018).…”
Section: Clinical Application Of Epigenetic Biomarker In Liquid Biopsmentioning
confidence: 99%
“…19,20 Many studies reported that abnormal DNA methylation correlates with tumor aggressiveness, tumor stage, and prognosis. [21][22][23] Aberrant DNA methylations in plasma are emerging biomarkers for liquid biopsy. In this study, we evaluated whether the detection of SHOX2 and PTGER4 methylation levels in serum would benefit the differential diagnosis of lung nodule found in LDCT screening.…”
Section: Discussionmentioning
confidence: 99%